2021
DOI: 10.48550/arxiv.2108.00431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The distribution of spacings of real-valued lacunary sequences modulo one

Abstract: Let (an) ∞ n=1 be a lacunary sequence of positive real numbers. Rudnick and Technau showed that for almost all α ∈ R, the pair correlation of (αan) ∞ n=1 mod 1 is Poissonian. We show that all higher correlations and hence the nearest-neighbour spacing distribution are Poissonian as well, thereby extending a result of Rudnick and Zaharescu to real-valued sequences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…An exception is the work of Yesha and the second named author [TY20], who showed that (n α mod 1)n has Poissonian m-point correlation, for almost all α > 4m 2 − 4m−1. Moreover, for lacunary sequences we refer to Rudnick and Zaharescu [RZ99, RZ02], for dilations of lacunary integer sequences; and Chaubey and Yesha [CY21] where this is extended to dilations of real-valued sequences.…”
Section: Historymentioning
confidence: 99%
“…An exception is the work of Yesha and the second named author [TY20], who showed that (n α mod 1)n has Poissonian m-point correlation, for almost all α > 4m 2 − 4m−1. Moreover, for lacunary sequences we refer to Rudnick and Zaharescu [RZ99, RZ02], for dilations of lacunary integer sequences; and Chaubey and Yesha [CY21] where this is extended to dilations of real-valued sequences.…”
Section: Historymentioning
confidence: 99%